Kidney tonifying traditional Chinese medicine: Potential implications for the prevention and treatment of osteoporosis - Duan, Yan; Su, Yu-Ting; Ren, Jie; Zhou, Qun; Tang, Min; Li, Juan; Li, Shun-Xiang (Frontiers in Pharmacology, 2023)
The aging global population leads to osteoporosis (OP), which is one of the most significant threats to the elderly. Moreover, its prevention and treatment situation have become increasingly severe. Therefore, it is imperative to develop alternatives or complementary drugs for preventing and treating OP. Kidney tonifying traditional Chinese medicine (KTTCM) has been used for the treatment of OP for a long history. Pharmacological studies have shown that KTTCM are promoters for the proliferation of osteoblasts, inhibitors for the activity of osteoclasts, regulators for the estrogen level and its receptor, plays important roles in stimulating osteogenesis, suppressing adipogenesis of marrow mesenchymal stem cells (MSCs), regulating metabolism of calcium and phosphorus, as well as inhibiting oxidative stress. These effects are mediated by OPG/RANKL/RANK, BMP/Smads, MAPKs and Wnt/β-Catenin systems. To develop standardized, synergistic, safe and effective TCM formula with robust scientific evidence to provide faster and more economical alternatives, the anti-osteoporosis ingredients and pharmacological mechanisms of KTTCM are summarized from the perspective of molecular and cell biology, and the safety and toxicity of KTTCM have also been reviewed in this paper.